STUDIES ON EFFECT OF PIPERINE ON ORAL BIOAVAILABILITY OF AMPICILLIN AND NORFLOXACIN - Janakiraman, Kunchithapatham; Manavalan, Rajappan (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
Ampicillin and Norfloxacin are used to treat variety of bacterial infections. These two drugs have low oral bioavailability. Co-administration of Piperine (20mg/kg), an alkaloid from Piper nigrum L. enhanced oral bioavailability of Ampicillin and Norfloxacin in animal model. This is reflected in various pharmacokinetic measurements like Cmax, Tmax, AUC and t½ of the above antibiotics in animal model.